Impact of the Basic Psychological Needs in Subjective Happiness, Subjective Vitality and Physical Activity in an Elderly Portuguese Population - Couto,Nuno (2017)
The goal of this work is to analyze the impact of elderly Portuguese individuals global perception of satisfying basic psychological needs in the areas of subjective happiness, subjective vitality and physical activity through a structural equations model. The way of well-being differs according to the amount of physical activity practiced in Portuguese elderly was also analyzed. Participants included 309 elderly people (242 females, 67 males) of Portuguese nationality who practice different levels of physical activity. Their ages range from 60 to 90 years old (M=68.59; DP=6.60). The obtained results show that the perception of basic psychological needs in Portuguese elderly peoples lives are a positive predictor of subjective happiness and subjective vitality. Also, the results verified that elderly people who perceive higher levels of competence practice more physical activity. Consequently, it is also possible to conclude that elderly people who participate in more physical activities perceive greater levels of subjective happiness and subjective vitality.